TIPS MERAIH UNTUNG BERLIPAT GANDA DALAM BISNIS RITEL - -, Lamidi - (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2011)
ABSTRACT Any business owner would want the maximum benefit from his efforts, so did the retail business. This article examines 12 Tips to manage the retail business to achieve profits doubled. “Tips Achieve Good thing doubled in Retail Business" was written based on the author's own experience that even some store owners who never visit the authors also say the same about their success. To achieve more profit, 12 tips can be applied by readers who are or start a business in the retail business. Keywords: retail business, success, marketing.